Development of the accounting practicum e-book and analysis of student responses to its use - Chin, Shi; Salam, Urai; Warneri, Warneri; Wicaksono, Luhur; Karolina, Venny (STAI Auliaurrasyidin Tembilahan, 2024)
This study aims to develop an E-Book for accounting practicum and evaluate user responses to its implementation. A needs analysis revealed that 48 out of 51 students lacked access to learning resources and required instructional media, correlating with their suboptimal learning outcomes. The research utilizes a Research and Development (R&D) approach, specifically employing the 4D model. The Technology Acceptance Model (TAM) Questionnaire was administered to gauge user feedback. The participants included 51 eleventh-grade students from SMKS Filadelfia Pemangkat. Data analysis involved both qualitative and quantitative descriptive methods to address the research questions regarding the E-Book's design, user feedback, and any significant disparities in responses based on socio-economic status. The E-Book, developed using Canva and edited with Heyzine, comprises 2 chapters, 4 videos, 2 Excel files, and 2 online quizzes. User responses from small and large group trials were overwhelmingly positive, categorized as